X-ray polarimetry of the accreting pulsar GX 301-2 - Suleimanov Valery F.; Forsblom Sofia V.; Tsygankov Sergey S.; Poutanen Juri; Doroshenko Victor; Doroshenko Rosalia; Capitanio Fiamma; Di Marco Alessandro; Gonzalez-Caniulef Denis; Heyl Jeremy; La Monaca Fabio; Lutovinov Alexander A.; et al. (EDP Sciences, 2025)
The phase- and energy-resolved polarization measurements of accreting X-ray pulsars (XRPs) allow us to test different theoretical models of their emission, and they also provide an avenue to determine the emission region geometry. We present the results of the observations of the XRP GX 301−2 performed with the Imaging X-ray Polarimetry Explorer (IXPE). A persistent XRP, GX 301−2 has one of the longest spin periods known: ∼680 s. A massive hyper-giant companion star Wray 977 supplies mass to the neutron star via powerful stellar winds. We did not detect significant polarization in the phase-averaged data when using spectro-polarimetric analysis, with the upper limit on the polarization degree (PD) of 2.3% (99% confidence level). Using the phase-resolved spectro-polarimetric analysis, we obtained a significant detection of polarization (above 99% confidence level) in two out of nine phase bins and a marginal detection in three bins, with a PD ranging between ∼3% and ∼10% and a polarization angle varying in a very wide range from ∼0 ◦ to ∼160◦ . Using the rotating vector model, we obtained constraints on the pulsar geometry using both phase-binned and unbinned analyses, finding excellent agreement. Finally, we discuss possible reasons for a low observed polarization in GX 301−2.